Breeding Success of Edible-Nest Swiftlets in a Man Made Nesting Habitat - Ani Mardiastuti; Yeni A Mulyani; Tiurmaida A.C Gultom (Media Konservasi, 1997)
The Edible-nest Swiftlet (Collocalia&ciphaga) has beenreceiving more attention lately due to the fact that this birdproduce an edible nests which fetch a high value in the international market. The original nesting habitat of this species islimestone caves. Since approximately a hundred year ago,people of Java has been successfully farmed the swiftlets inhouses which managed in such a way to resemble natural cavehabitat (Mardiastuti, 1996).There has been no previous study on the breeding ecologyof the Edible-nest Swiftlet in Indonesia, either in natural cavehabitats or in man-made nesting habitat. This paper aims toreveal the breeding success of the species and investigate thepossible causes of the breeding failure in swiftlet houses.